A formação de professores e os desafios do ensino/aprendizagem em períodos de mudanças sociais - Perin, Conceição Solange Bution; Mendes, Claudinei Magno Magre [UNESP] (Universidade Estadual de Maringa, 2013)
The objective of this paper is to present the relationship between higher education with other levels of education. In Brazil, some challenges were launched to fulfill improvement in teaching / learning covering a scientific development with the involvement of several bodies, among them the science and society. Therefore, according to the National Postgraduate-PNPG, the close relationship between science and society requires a scientific-cultural training that should start in higher education, teacher training, and that this knowledge can follow the company, traversing all levels of education prior to higher education. Thus, we analyze the formation of teachers as one of the pillars of our discussion, trying to understand that at different times, men have paid attention to the re/organization of society, to masters/teachers have the knowledge that enabled individuals to convey an apprenticeship favoring the theoretical reflection on practice. So, we have considered some classics, as Bonaventure of Bagnoregio, that dealt on the training of teachers (as) in different periods, expressing concern about the quality of teaching and documents dealing with the situation of education in Brazil

O objetivo deste trabalho é apresentar as relações existentes entre o ensino superior com os demais níveis de ensino. No Brasil, alguns desafios foram lançados para o cumprimento de melhoria no ensino/aprendizagem que abrange um desenvolvimento científico com o envolvimento de várias instâncias, dentre elas, a ciência e a sociedade. Para tanto, segundo o Plano Nacional de Pós-Graduação- PNPG, a estreita relação entre ciência e sociedade requer uma formação cultural-científica que deve ter início no ensino superior, com a formação de professores, e que esses conhecimentos possam acompanhar a sociedade, perpassando todos os níveis de ensino que antecedem a formação superior. Dessa forma, analisaremos a formação de professores como um dos eixos da nossa discussão, procurando entender que em diferentes momentos, homens se atentaram para a re/organização da sociedade, no sentido de mestres/professores terem o conhecimento que possibilitava transmitir aos indivíduos um aprendizado teórico que favorecesse a reflexão na prática. Assim, nos fundamentamos em alguns clássicos, como Boaventura de Bagnoregio (1217-1274), que trataram sobre a formação de professores (as) em períodos distintos, expressando a preocupação com a qualidade no ensino e em documentos que tratam sobre a situação da educação no Brasil.
Teacher education and the challenges of teaching/learning in social changes periods
Keywords: The objective of this paper is to present the relationship between higher education with other levels of education. In Brazil, some challenges were launched to fulfill improvement in teaching / learning covering a scientific development with the involvement of several bodies, among them the science and society. Therefore, according to the National Postgraduate-PNPG, the close relationship between science and society requires a scientific-cultural training that should start in higher education, teacher training, and that this knowledge can follow the company, traversing all levels of education prior to higher education. Thus, we analyze the formation of teachers as one of the pillars of our discussion, trying to understand that at different times, men have paid attention to the re/organization of society, to masters/teachers have the knowledge that enabled individuals to convey an apprenticeship favoring the theoretical reflection on practice. So, we have considered some classics, as Bonaventure of Bagnoregio, that dealt on the training of teachers (as) in different periods, expressing concern about the quality of teaching and documents dealing with the situation of education in Brazil; História e Política; Cultura; Formação de professores; História; Debates políticos; Projetos políticos